2012
DOI: 10.1002/asia.201101046
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilicities of Bissulfonyl Ethylenes

Abstract: Kinetics of the reactions of bissulfonyl ethylenes with various carbanions, a sulfur ylide, and siloxyalkenes have been investigated photometrically at 20 °C. The second-order rate constants have been combined with the known nucleophile- specific parameters N and s(N) for the nucleophiles to calculate the empirical electrophilicity parameters E of bissulfonyl ethylenes according to the linear free energy relationship log k(20 °C)=s(N)(N+E). Structure-reactivity relationships are discussed, and it is shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…, the E parameters of the thiophene series 1a–d cover a domain of electrophilic reactivity of 4 orders magnitude from the weakest electrophile 1d ( E = −21.33) to the strongest ones 1a ( E = −17.18). Figure also reveals that the thiophenes 1a–d used in this study display an electrophilicity that compares well with that of 4‐(2,2‐bis‐(phenylsulphonyl)vinyl)‐ N , N ‐dimethylaniline 9 ( E = −16.53) , the substituted pyridinium salt 10 ( E = −17.90) , the 3‐methoxybenzaldehyde 11 ( E = −19.32) , and the diethyl 4‐methyl‐benzylidenemalonate 12 ( E = −21.11) , respectively, but lower than that of 1,3,5‐trinitrobenzene 8 ( E = −13.19) , the conventional aromatic electrophile in S N Ar processes and the 3,5‐difluoro‐substituted benzhydrylium ion 5 ( E = 8.02), the most electrophilic species known to date . Within the E scale developed by Mayr and co‐workers, the electrophilicity of the most reactive thiophene, i.e., 1a ( E = −17.18) appears to be higher than that of some benzylidenemalonate such as the substituted diethyl benzylidenemalonate 4 ( E = −23.80), but have an E value lower by 11 units than that of 7‐chloro‐4,6‐dinitrobenzofuroxan 6 and 7‐chloro‐4,6‐dinitrobenzofurazan 7 ( E = −6.11) .…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…, the E parameters of the thiophene series 1a–d cover a domain of electrophilic reactivity of 4 orders magnitude from the weakest electrophile 1d ( E = −21.33) to the strongest ones 1a ( E = −17.18). Figure also reveals that the thiophenes 1a–d used in this study display an electrophilicity that compares well with that of 4‐(2,2‐bis‐(phenylsulphonyl)vinyl)‐ N , N ‐dimethylaniline 9 ( E = −16.53) , the substituted pyridinium salt 10 ( E = −17.90) , the 3‐methoxybenzaldehyde 11 ( E = −19.32) , and the diethyl 4‐methyl‐benzylidenemalonate 12 ( E = −21.11) , respectively, but lower than that of 1,3,5‐trinitrobenzene 8 ( E = −13.19) , the conventional aromatic electrophile in S N Ar processes and the 3,5‐difluoro‐substituted benzhydrylium ion 5 ( E = 8.02), the most electrophilic species known to date . Within the E scale developed by Mayr and co‐workers, the electrophilicity of the most reactive thiophene, i.e., 1a ( E = −17.18) appears to be higher than that of some benzylidenemalonate such as the substituted diethyl benzylidenemalonate 4 ( E = −23.80), but have an E value lower by 11 units than that of 7‐chloro‐4,6‐dinitrobenzofuroxan 6 and 7‐chloro‐4,6‐dinitrobenzofurazan 7 ( E = −6.11) .…”
Section: Methodssupporting
confidence: 60%
“…The E values are listed and compared in Fig. with those obtained in previous studies by Terrier and co‐workers for 7‐chloro‐4,6‐dinitrobenzofuroxan 6 , 7‐chloro‐4,6‐dinitrobenzofurazan 7 , and 1,3,5‐trinitrobenzene 8 , together with substrates 4 , 5 , and 9–12 previously investigated by Mayr and co‐workers .…”
Section: Methodsmentioning
confidence: 95%
“…for the reaction of thiophene 2 with the CH 3 O − ion in methanol is 11.6 times larger than calculated (k2 calc ) according to Equation . The deviations between calculated rate constants from the three parameters (Equation ) and experimental rate constants have been observed by many authors . Zenz and co‐workers investigated the reactivities of a series of trans ‐ β ‐nitrostyrenes with various acceptor‐substituted carbanions in dimethyl sulfoxide solution at 20°C and demonstrated that calculated rate constants according to the linear free energy relationship (Equation ) deviate by less than a factor of 6 from those measured.…”
Section: Resultsmentioning
confidence: 98%
“…This stability can also be evaluated by using the "methyl cation affinity" (MCA), a thermodynamic parameter that is easily and accurately calculated, [20] which represents the energy necessary to strip off a methyl cation from the corresponding methylammonium species. [23] Catalyst Clearly, in this transformation the Lewis-basic character of the catalyst is a key parameter to achieve good conversions. Table 3.…”
Section: Resultsmentioning
confidence: 99%